Comparison of the Diagnostic Value of Fine Needle Aspiration and Frozen Section in Patients with Thyroid Nodule Surgery Referring to Babol University of Medical Sciences Hospitals between 2011 and 2019 - Novin Nikbakhsh; Amir Morteza Rezazadeh; Ali Bijani; Sekineh Kamali Ahangar; Mohammad Rnaee (مجله علمی دانشگاه علوم پزشکی کردستان)
Background and Aim: Thyroid nodules are among common clinical problems and fine needle aspiration (FNA) sampling is the most important method to diagnose its pathological nature. The frozen section (FS) is also very important in making treatment decisions. The present study was conducted to compare the diagnostic value of these two methods based on pathology findings in the patients with thyroid nodules. Materials and Methods: This descriptive-analytical study included patients with thyroid nodule surgery between 2011 and 2019 in Babol City. Information was collected by file reading method. Data analysis was done using SPSS-26 software and a comparative survey of the diagnostic value of pathology methods, FNA biopsy, and FS examination, was performed by calculating the sensitivity, specificity, and positive and negative predictive value (p<0.05). Results: The majority of patients in this study were female (68.66%) and the patients did not have any family history (70.44%). In the final pathology findings, the rates of benign and malignant lesions were; 54.88% and 45.11%, and in FNA and FS, they were 67% and 88.57%, respectively. Sensitivity, specificity, positive and negative predictive values in FNA were; 0.9582, 0.9896, 0.9950, and 0.9697, respectively. Sensitivity, specificity, positive and negative predictive value in FS were 100%. The two mentioned methods were consistent in 58.8% of the cases in the diagnosis of malignant or benign thyroid nodules (p<0.001). Conclusions: FNA is a reliable method for detecting malignancy in thyroid nodules due to its high sensitivity and specificity. On the other hand, the FS is considered a precise method due to its high correlation with pathology.